2001
DOI: 10.1002/jnr.1096
|View full text |Cite
|
Sign up to set email alerts
|

Local synthesis of nuclear‐encoded mitochondrial proteins in the presynaptic nerve terminal

Abstract: One of the central tenets in neuroscience has been that the protein constituents of distal compartments of the neuron (e.g., the axon and nerve terminal) are synthesized in the nerve cell body and are subsequently transported to their ultimate sites of function. In contrast to this postulate, we have established previously that a heterogeneous population of mRNAs and biologically active polyribosomes exist in the giant axon and presynaptic nerve terminals of the photoreceptor neurons in squid. We report that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 28 publications
4
91
0
Order By: Relevance
“…The low level of contaminating structures was confirmed by light and EM autoradiographic analyses, which also demonstrated the nearly exclusive localization of newly synthesized proteins in large synaptosomes (58). Polysomes purified from optic lobe synaptosomes incubated with [ 35 S]methionine were shown to contain nascent peptide chains (57), and to be free from microsomal polysomes (110). Polysomes were likewise identified in the large optic lobe synaptosomes using ESI (Fig.…”
Section: Squid Nerve Endingsmentioning
confidence: 69%
See 1 more Smart Citation
“…The low level of contaminating structures was confirmed by light and EM autoradiographic analyses, which also demonstrated the nearly exclusive localization of newly synthesized proteins in large synaptosomes (58). Polysomes purified from optic lobe synaptosomes incubated with [ 35 S]methionine were shown to contain nascent peptide chains (57), and to be free from microsomal polysomes (110). Polysomes were likewise identified in the large optic lobe synaptosomes using ESI (Fig.…”
Section: Squid Nerve Endingsmentioning
confidence: 69%
“…RT-PCR analyses of synaptosomal polysomes have led to the identification of mRNAs coding for cytoskeletal and ribosomal proteins, translation factors and, most notably, mitochondrial proteins encoded by nuclear DNA (110,111). The association of these mRNAs with purified polysomes indicates that the corresponding proteins are synthesized in presynaptic synaptosomes.…”
Section: Squid Nerve Endingsmentioning
confidence: 99%
“…Localized synthesis of HSP70 has been shown in presynaptic nerve terminals from squid optic lobe (Gioio et al, 2001;Jimenez et al, 2002), and the mRNA of Hsc70, a constitutively expressed HSP70 family member, has been detected in dendrites (Foster and Brown, 1996). Localized synthesis of other HSPs has not been reported previously.…”
Section: Axonal Synthesis Of Heat Shock Proteinsmentioning
confidence: 82%
“…However, almost all the genes that encode mitochondrial proteins reside in the nuclear genome within the cell body, so full biogenesis in the axon would require anterograde axonal transport of hundreds of different mitochondrial proteins, or their mRNAs. Axoplasm has a modest translation capacity (Lee and Hollenbeck, 2003) and some mitochondrial protein synthesis can occur there (Gioio et al, 2001;Martin et al, 1998;Sotelo-Silveira et al, 2006). Axonal mRNA microarray analysis and quantitative PCR have shown that axons can contain many mitochondrial mRNAs, some at concentrations as high as 10% of their levels measured in the cell body (Taylor et al, 2009).…”
Section: Localized Biogenesis Of Mitochondriamentioning
confidence: 99%